2006
DOI: 10.1016/j.agrformet.2006.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Estimating sensible and latent heat fluxes over rice using surface renewal

Abstract: The performance of surface renewal (SR) analysis for estimating sensible (H) and latent (λE) heat fluxes has been analysed over a sprinkler irrigated rice. Similarity principles were not fully met during the experiment and the (H+λE) measured values with the eddy covariance did not close the surface energy-balance. H and λE estimates using SR analysis were reliable and provided a reasonable energy-balance closure. The Bowen ratio was also estimated using SR analysis. Good estimates were obtained though mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…Since the H from SR was quite similar to H from EC, it also implies that the lack of closure is likely due to the EC measurement of LE. Castellví et al (2006) also reported good closure for SR measurements over rice and poor closure for EC measurements over rice. Thus, using the REB method to determine ET c and K c values seems much more reasonable than direct usage of LE from EC measurements.…”
Section: Evapotranspiration and Crop Coefficientsmentioning
confidence: 96%
“…Since the H from SR was quite similar to H from EC, it also implies that the lack of closure is likely due to the EC measurement of LE. Castellví et al (2006) also reported good closure for SR measurements over rice and poor closure for EC measurements over rice. Thus, using the REB method to determine ET c and K c values seems much more reasonable than direct usage of LE from EC measurements.…”
Section: Evapotranspiration and Crop Coefficientsmentioning
confidence: 96%
“…In this study, EBC was principally evaluated by performing a regression analysis (e.g. see Wilson and Baldocchi, 2000;Wilson et al, 2002;Castellvi et al, 2006). The linear regression coefficients (slope and intercept) as well as the coefficient of determination (R 2 ) were calculated from the ordinary least squares (OLS) relationship between the 30 min estimates of the dependent flux variables (LE+H ) and the independently derived available energy (R net −G−S).…”
Section: Data Set Pre-processingmentioning
confidence: 99%
“…Besides some of the technical limitations related to the required horizontal homogeneity of the surface layer, measurement methods for determining H such as EC, Bowen ratio energy balance (BREB), 3,8,[14][15][16] surface renewal (SR), [17][18][19][20] and others are also very expensive if used at multiple points or locations for wider areas since that would require a number of such units. 10,21 The scintillometer method has been applied and tested by several authors 1,3,4,9,10,[21][22][23] and studies carried out in the past have revealed that the scintillometer method is an attractive alternative to the commonly-used measurement methods, such as EC, for the estimation of H and τ.…”
Section: R Le H Smentioning
confidence: 99%